Mobilities at the service of urban heritage, scenarios for the tourism in Old Mila - Adjeroud, Heythem (Milev Journal of Research and Studies, 2019)
This work deals with the subject of the historical center of Old Mila, and tries through the reading and the analysis of available data and historical facts, to identify the best routes in order to guarantee the emergence within it of an urban and socioeconomic dynamic which will become a lever for the safeguarding of its urban heritage. The aim of this study is to shed light on an interesting opportunity to build a project around urban heritage through tourism development, the museumization of monuments and creating touristic circuits.